Purkinje Cell Ataxin-1 Modulates Climbing Fiber Synaptic Input in Developing and Adult Mouse Cerebellum - Ebner, Blake A. (Society for Neuroscience, 2013)
Previous studies indicate that while transgenic mice with ATXN1[30Q]-D776-induced disease share pathological features caused by ATXN1[82Q] having an expanded polyglutamine tract, they fail to manifest the age-related progressive neurodegeneration seen in spinocerebellar ataxia type 1. The shared features include morphological alterations in climbing fiber (CF) innervation of Purkinje cells (PCs). To further investigate the ability of ataxin-1 (ATXN1) to impact CF/PC innervation, this study used morphological and functional approaches to examine CF/PC innervation during postnatal development in ATXN1[30Q]-D776 and ATXN1[82Q] cerebella. Notably, ATXN1[30Q]-D776 induced morphological alterations consistent with the development of the innervation of PCs by CFs being compromised, including a reduction of CF translocation along the PC dendritic tree, and decreased pruning of CF terminals from the PC soma. As previously shown for ATXN1[82Q], ATXN1[30Q]-D776 must enter the nucleus of PCs to induce these alterations. Experiments using conditional ATXN1[30Q]-D776 mice demonstrate that both the levels and specific timing of mutant ATXN1 expression are critical for alteration of the CF–PC synapse. Together these observations suggest that ATXN1, expressed exclusively in PCs, alters expression of a gene(s) in the postsynaptic PC that are critical for its innervation by CFs. To investigate whether ATXN1[30Q]-D776 curbs the progressive disease in ATXN1[82Q]-S776 mice, we crossed ATXN1[30Q]-D776 and ATXN1[82Q]-S776 mice and found that double transgenic mice developed progressive PC atrophy. Thus, the results also show that to develop progressive cerebellar degeneration requires expressing ATXN1 with an expanded polyglutamine tract.